Thermo-hydraulic performance of nanofluids in a bionic heat sink. (October 2021) - Tang, Jinghua; Qi, Cong; Ding, Zi; Afrand, Masoud; Yan, Yuying
Abstract: A bionic surface based on the wing structure of the dragon louse is developed and applied in the thermal management system of electronic components. Fe3 O4 -water nanofluids are introduced and their thermal-hydrodynamic behaviors under magnetic field are studied. The influence of nanofluids concentration ( ξ  = 0.1–0.5%), Reynolds numbers ( Re  = 712–1400), tilt angles of magnetic field ( θ  = 0°, 30°, 60°) and intensity of magnetic field ( β  = 0.0 T, 0.005 T, 0.010 T, 0.015 T) on the heat transfer are considered in the system. Exergy efficiency and entropy production of CPU cooling system are analyzed. Results presented that the bionic surface based on the wing structure of the dragon louse shows an excellent drag reduction effect compared with the smooth surface, which can reach 35.4%. The maximal reduced ratio of CPU surface temperature under magnetic field is 34.42% in comparison with that under no magnetic field, and the maximal reduced ratio of CPU surface temperature with θ  = 60° is 14.96% in comparison with θ  = 0°. It shows an augmentation of heat transfer for most cases with the identical rate of flow from the point of exergy efficiency. When nanofluids concentration is ξ  = 0.3%, Reynolds number is Re  = 1402, tilt angle is θ  = 60°, and magnetic field strength is β  = 0.015 T, the minimum entropy production is obtained.